Batas Kewenangan Direksi dan Dewan Komisaris dalam Pengelolaan Perusahaan Berkaitan dengan Dicabutnya Izin Usaha Pertambangan: Studi Kasus Putusan No.3/Pdt.G/2023/PN Mgg - Santika, Charisa Dwi; Suryanti, Nyulistiowati; Mantili, Rai (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The limits of authority among the company’s organs in corporate management are expressly regulated under the UUPT, which assigns managerial and representative functions to the Board of Directors, supervisory and advisory functions to the Board of Commissioners, and control functions to the General Meeting of Shareholders. In practice, these authorities are often not implemented effectively, resulting in various violations. Such violations do not always arise from ultra vires acts but may also stem from negligence in exercising the granted authority. Improper management, administrative omissions, and passive supervision contribute to the risk of loss upon revocation of a mining business license. The absence of a valid license removes the company’s legal basis for operating and triggers potential liability for he organs that were negligent. This research employs a normative juridical approach with a descriptive-analytical specification. Data were obtained from primary, secondary, and tertiary legal materials through literature review and case study of Decision No. 3/Pdt.G/2023/PN.Mgg. Directors must distinguish between beheer and beschikking actions when determining the scope of corporate management. Meanwhile, the Board of Commissioners is obligated to conduct supervision and provide advice proactively, whether requested or not, as a manifestation of good faith.